Panicle surface area as a selection criterion for grain yield in pearl millet (Pennisetum glaucum) - SOLANKI, Y P S; KHAIRWAL, I S; BIDINGER, F R (The Indian Journal of Agricultural Sciences, 2014)
In an experiment 24 experimental varieties of 3 composites, viz 'EC 87', 'EC 91' and 'HHVBC', were evaluated during rainy season of 1996 and 1997 in 11 environment at 3 locations for the effect of selection for panicle surface area on grain yield and its components in pearl millet [Pennisetum glaucum (L.) R. Br. emend. Stuntz]. Singificant variation was observed among experimental varieties for all the traits, The actual gain in 'PCV 5' (with maximum panicle surface area) over the original population was 8.7% for grain yield/m across the composites. Breeder selection was effective in improving grains/m by an average of 4% in 3 composited, but it was effective in improving grain yield/m over the original population by 3% in 'EC 91; only. The net increase in grain yield/m was almost similar to the prediction (+8.7% vs prediction of 10%). Also the selection for large panicle surface area, ie 'PCV 5', was more effective than breeder selection for grain yield/m by an average of 9% in the 3 composites, The panicle surface area showed positive correlation with grain number/m, grain size and grain yield/m among experimental varieties (PCV 1' to PCV 5') in 3 populations.